Vinogradovopleustes punctatum, new genus, new species, a pleustid amphipod from the Okhotsk Sea (Crustacea: Amphipoda: Gammaridea: Pleustidae: Pleusymtinae) - Labay, Vjacheslav S. (Zootaxa, 2018)
The new genus Vinogradovopleustes gen. nov. and new species V. punctatum sp. nov. are described from the shelf of northern Sakhalin Island. A key to the amphipod genera of the subfamily Pleusymtinae Bousfield & Hendrycks, 1994 is given.